2002
DOI: 10.1021/tx015546t
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Conjugation and DNA Adduct Formation of Dibenzo[a,l]pyrene and Benzo[a]pyrene Diol Epoxides in V79 Cells Stably Expressing Different Human Glutathione Transferases

Abstract: Mammalian V79 cells stably expressing human glutathione transferase (GST) A1-1, M1-1, and P1-1 (the allelic variant with Val105 and Ala114) have been constructed and characterized. The cells have been used to study the capacity of individual GST isoenzymes in conjunction with GSH to detoxify diol epoxides from dibenzo[a,l]pyrene (DBPDE), the most carcinogenic polycyclic aromatic hydrocarbon (PAH) identified so far, and diol epoxides from benzo[a]pyrene (BPDE). The relationship between GSH-conjugation and DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 56 publications
4
67
0
Order By: Relevance
“…The authors caution against extrapolating catalytic information from pure enzymes to the complex situation within the intact cell. Notably, they found only about 1 -2% of the expected rate of BPDE conjugation to be observed in vivo in cells, which the authors postulate may be a result of the reduced concentrations of lipophilic substrates available for conjugation by the soluble GSTs (Sundberg et al, 2002).…”
Section: Metabolic Polymorphismsmentioning
confidence: 96%
See 1 more Smart Citation
“…The authors caution against extrapolating catalytic information from pure enzymes to the complex situation within the intact cell. Notably, they found only about 1 -2% of the expected rate of BPDE conjugation to be observed in vivo in cells, which the authors postulate may be a result of the reduced concentrations of lipophilic substrates available for conjugation by the soluble GSTs (Sundberg et al, 2002).…”
Section: Metabolic Polymorphismsmentioning
confidence: 96%
“…A re-examination of GSTP1 genotype -phenotype relationships (Sundberg et al, 2002) has suggested that the GSTP1 enzyme containing valine at position 105 may actually have less than, or at most equal activity in reducing, PAH -DNA adduct formation compared with the wildtype GSTP1 Ile105/Ala114 isoform. The authors caution against extrapolating catalytic information from pure enzymes to the complex situation within the intact cell.…”
Section: Metabolic Polymorphismsmentioning
confidence: 99%
“…The metabolic intermediates of benzo[a]pyrene, 7,8-epoxide and trans -7,8-diol, as well as the two stereoisomeric diol epoxides (syn-and anti-BPDE) are all optically active. Glutathione conjugates (for detoxification) also display optical activity [12]. The frequency and ratio of stereoisomeric BPDE-DNA adducts, the endpoint of metabolic intermediates, can be used as a stereochemical indicator of these optically active intermediates if the developed analytical method has adequate sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…GSTs encoded by polymorphic members of the mu (GSTM1), pi (GSTP1) and theta (GSTT1) gene families play important roles in the detoxication of a variety of reactive toxic and carcinogenic compounds, including PAH epoxides and diol epoxides (Hecht, 2002a). Isoforms involved in the formation of glutathionyl conjugates with PAH diol epoxides have been assigned (Jernström et al, 1996;Sundberg et al, 1998Sundberg et al, , 2002 and their rank order of importance based on catalytic efficiency (catalytic constant (k cat )/Michaelis constant (K m )) varies by PAH diol epoxide and individual stereochemistry. For example, for the conjugation of the (-)-anti-diol epoxide dibenzo [a,l]pyrene (R-configuration at the benzylic oxirane carbon in the fjord-region), the preference is GSTA1-1 > GSTM1-1 > GSTP1-1.…”
Section: (X) Epoxide Hydrolasementioning
confidence: 99%